The Effect of Integration of Family Planning Into HIV Services on Contraceptive Use Among Women Accessing HIV Services in Low and Middle-Income Countries: A Systematic Review - Grant-Maidment, Tallulah; Kranzer, Katharina; Ferrand, Rashida A. (Frontiers in Global Women's Health, 2022)
There is substantial unmet need for family planning (FP) among women living with HIV (WLHIV), leading to unintended pregnancies and may contribute indirectly to increasing the risk of transmission of HIV. This review aims to determine whether integration of FP into HIV testing and care results in increased use of contraception, a reduction in unmet need for FP, improved use of safer conception methods and a reduction in unintended pregnancies in low and middle-income countries. A systematic review was undertaken incorporating studies from PubMed, EMBASE, CINAHL, Web of Science and Global Health, the International AIDS Society Abstract Archive, the World STI & HIV Congress Abstract Archive and the Conference on Retroviruses and Opportunistic Infections Abstract Archive published between 2016 and 2021, updating previous systematic reviews. After screening, 13 studies were included, 11 conducted in sub-Saharan Africa and 2 in India. The primary outcome of the review was contraceptive uptake and secondary outcomes included unmet need for FP, safer conception and unintended pregnancy. Integrated FP-HIV facilities were found to increase dual contraceptive use by at least 8% in five studies and modern contraceptive use by at least 8% in four studies. Findings from two studies suggested integration decreased the unmet need for contraception. Limited data prevented a conclusion from being drawn regarding whether integration increases safer conception. There was no evidence of integration reducing unintended pregnancies. The median quality score of studies was 3/9. Overall, integrated facilities have the potential of improving reproductive health of women accessing HIV services in LMICs. FP may be enhanced by including a safer conception component for WLHIV.